Scripts in Organizational Behavior - Gioia, Dennis A.; Poole, Peter P. (Academy of Management Review, 1984)
The concept of a “script” is presented as a framework for understanding the cognitive dynamics underlying many organizational behaviors and actions. A script is a schematic knowledge structure held in memory that specifies behavior or event sequences that are appropriate for specific situations. “Script processing” is the performance of the behaviors or events contained in the knowledge structure. Many facets of organizational behavior can be effectively described, analyzed, and understood by using the script concept and processing notion.